The gasteruptiid wasp fauna of New Caledonia, with description of three new species of Gasteruption (Hymenoptera: Evanioidea: Gasteruptiidae) - Jennings, John T.; Jourdan, Hervé; Krogmann, Lars; Parslow, Ben A. (Zootaxa, 2016)
The rarely collected gasteruptiid wasp fauna (Evanioidea: Gasteruptiidae) of New Caledonia is reviewed. Previously only two species of Pseudofoenus (Hyptiogastrinae) were known. Here, we record the subfamily Gasteruptiinae from New Caledonia for the first time and describe three new species of Gasteruption: G. lacoulee Jennings, Krogmann & Parslow, sp. nov., G. maquis Jennings, Krogmann & Parslow, sp. nov., and G. sarramea Jennings, Krogmann & Parslow, sp. nov. An identification key to the Gasteruptiidae of New Caledonia is provided.